2004
DOI: 10.1002/ijc.20729
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 expression reflects tumor progression and regulates motility of bladder cancer cells

Abstract: Transitional cell carcinoma of the urinary bladder remains life threatening due to the high occurrence of metastases. Emerging evidence suggests that chemokines and their receptors play a critical role in tumor metastases. In our study, we performed a systematic analysis of the mRNA and protein expression levels of all 18 chemokine receptors in normal urothelium and bladder cancer. CXCR4 was the only chemokine receptor whose mRNA expression level was upregulated in bladder cancer cell lines as well as in invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 30 publications
1
45
0
1
Order By: Relevance
“…Exposure of CXCR4-positive bladder cancer cells to its ligand (CXCL12) provoked a significant increase in proliferation as well as invasion across a Matrigel barrier in a Boyden chamber type assay (Eisenhardt et al, 2005;Retz et al, 2005). Consistently, enhanced migration and invasion were inhibited by a CXCR4-specific blocking antibody (Eisenhardt et al, 2005;Retz et al, 2005). Moreover, a recent study demonstrated that higher CXCR4 expression was associated with Stat3 signaling activation in bladder cancer [30].…”
Section: Discussionmentioning
confidence: 88%
“…Exposure of CXCR4-positive bladder cancer cells to its ligand (CXCL12) provoked a significant increase in proliferation as well as invasion across a Matrigel barrier in a Boyden chamber type assay (Eisenhardt et al, 2005;Retz et al, 2005). Consistently, enhanced migration and invasion were inhibited by a CXCR4-specific blocking antibody (Eisenhardt et al, 2005;Retz et al, 2005). Moreover, a recent study demonstrated that higher CXCR4 expression was associated with Stat3 signaling activation in bladder cancer [30].…”
Section: Discussionmentioning
confidence: 88%
“…Following their investigation, CXCR4 involvement in metastasis has been suggested in a variety of tumors and its expression in the primary site has been clinically correlated with poor survival or tumor progression in ovarian carcinoma, 2 neuroblastoma, 8 head and neck squamous cell carcinoma, 10 colorectal carcinoma 11 and urinary bladder cancer. 12 However, no investigators have compared CXCR4 expression in the primary site with that in the concordant metastatic site, using a rather large series of clinical samples. Moreover, no studies have evaluated CXCR4 expression in human sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Among chemokines and their receptors, the stromal cell-derived factor-1 (SDF-1/CXCL12)/CXCR4 system has been demonstrated to be involved in the lymph node metastasis or distant metastasis of several types of cancer. [1][2][3][4][5][6][7][8][9][10][11][12] Osteosarcoma is the most frequent primary bone tumor in young adults and adolescents. Despite recent advances in multimodality treatments consisting of adjuvant chemotherapy and surgical-wide resection, pulmonary metastasis occurs in approximately 40-50% of the patients.…”
mentioning
confidence: 99%
“…Retz et al (11) showed that bladder cancer cells express CXCR4 progressively with advanced tumorigenesis and that this receptor interacts with CXCL12 to mediate tumor chemotaxis and invasion through connective tissue. These properties identify CXCR4 as a potential target for the attenuation of bladder cancer metastases.…”
Section: Discussionmentioning
confidence: 99%